The interaction between nutrition and metabolism in West African Dwarf goats, infected with trypanosomes. - Dam, J.T.P. van (Wageningen University & Research, 1996)
In a series of experiments the interaction between nutrition and energy- and nitrogen metabolism of West African Dwarf goats, infected with trypanosomes was studied. Animals were injected with trypanosomes, and feed intake, energy and nitrogen balance and blood metabolites and hormones were measured for a period of six weeks post infection. Trypanosoma vivax infection caused fever and anaemia. The degree of anorexia, as indicated by the ratio [dry matter intake during infection / dry matter intake before infection] differed between experiments and between animals. Some indications were found for a relation between MHC genotype and dry matter intake ratio, but also environmental factors like stress and the age of the animals probably affected this ratio. Trypanosome infection caused a reduction of the energy retention, by decreasing gross energy intake and by increasing maintenance requirements with 28 %. This increased maintenance requirement was mainly related to the fever. Blood biochemical parameters reflected the undernourished state of infected animals. No indications were found for an interaction between the quality of the offered diet and the course of infection with respect to feed intake and nitrogen metabolism; instead, the effects of diet quality and of trypanosome infection were additive. Also no interaction occurred between nutritional history (as indicated by growth retardation which had developed prior to infection) and the course of subsequent trypanosome infection with respect to energy and nitrogen metabolism.